Harmonizing Confucianism in Nepali Education System: A Thematic Review (Journal of Musikot Campus, 2025)
The integration of Confucian progressive educational principles into the Nepali educational landscape is a topic of growing interest lately. This thematic review critically explores the necessity and effectiveness of integrating Confucian educational values to harmonize the Nepali education system. I utilized Systematic Literature Review (SLR) as a research method for collecting relevant papers available on the Google Scholar for the study. Scholarly papers (n=11) on Confucian philosophy and education were systematically selected, using the certain key words like “Confucianism”, “Confucius education principles” & “Nepali education system”. The papers were then reviewed and synthesized against the research questions. The study focused on how Confucianism can be effectively integrated in Nepali education system and what could be the potential benefits of adopting this philosophy in Nepali education system. The findings of the study revealed that incorporation of Confucian progressive value-based educational principles along with Western centric academic knowledge would harmonize Nepali educational landscape. The dynamic interplay between moral education and academic knowledge would enable for holistic development of the individuals. Additionally, adaptation of Confucian curriculum, pedagogy and cross-cultural understanding would be crucial strategies for harmonizing Confucianism in Nepalese education system. Just as China, Korea, Japan and Vietnam; Nepal can also make a significant progress both in social and education development in Nepal through adaptation of Confucian system. This study is significant because it encourages the educators, curriculum designers and policy makers to consider in adopting Confucian progressive value-based philosophy in Nepali education system.